New Studies on Hallucinogenic Mushrooms: History, Diversity, and Applications in Psychiatry - Gastón Guzmán Huerta (International Journal of Medicinal Mushrooms, 2015)
This paper is a review of the new studies or new explanations of the hallucinogenic mushrooms, regarding their diversity, history, traditions, and problems in their recreational use, new taxonomic studies, and their modern applications in medicine, all of them since the 1970s to the present.